Analisis Pembinaan Dalam Meningkatkan Skills Narapidana - Jihan Jihan; Nurhayati Nurhayati; Seflidiana Roza (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to find out how to train prisoners to improve their Skills at the Class IIB correctional institution in Solok City. The type of research used is descriptive qualitative. The data collection techniques used in this research were observation, interviews and documentation. The type of data used is qualitative and the data source uses primary data sources. The data analysis technique used in this research is a qualitative descriptive method. There were 12 informants used in this research, consisting of the Head of the Correctional Institution, prison officers, coaching mentors, prisoners and visitors. The results of the research show that the analysis of inmate coaching in improving Skills at the Class IIB correctional institution in Solok City, namely Self-Reliance Coaching, Self-Reliance Coaching, was carried out to provide skills and guide inmates in entrepreneurship which can later be used by the inmates if one day they return to the community. public. Apart from fostering independence in the field of skills, the Solok Class IIB Correctional Institution also has Personality Development. With Personality Development, it is hoped that inmates will have a change in attitude and be able to restore their self-esteem so they can integrate themselves into society after leaving prison.